2007
DOI: 10.1177/014107680710000716
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of spinal manipulation: a systematic review

Abstract: Spinal manipulation, particularly when performed on the upper spine, is frequently associated with mild to moderate adverse effects. It can also result in serious complications such as vertebral artery dissection followed by stroke. Currently, the incidence of such events is not known. In the interest of patient safety we should reconsider our policy towards the routine use of spinal manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
130
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(137 citation statements)
references
References 67 publications
2
130
1
4
Order By: Relevance
“…8 These findings do not argue against the use of such treatments but serve as reminders of limitations and possible harmful effects. The mean duration of pain in patients who seek treatment at chronic pain treatment facilities is approximately 7 years.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…8 These findings do not argue against the use of such treatments but serve as reminders of limitations and possible harmful effects. The mean duration of pain in patients who seek treatment at chronic pain treatment facilities is approximately 7 years.…”
mentioning
confidence: 98%
“…[3][4][5] In some studies, investigators reported that more than 40% of patients with implanted devices for pain control experience adverse events 6 ; up to 67.7% of patients treated with lumbar surgery for back pain reported that their pain was worse after surgery, 7 and at least moderate adverse effects have been reported to occur in 30% to 61% of all patients who undergo spinal manipulations. 8 These findings do not argue against the use of such treatments but serve as reminders of limitations and possible harmful effects. The mean duration of pain in patients who seek treatment at chronic pain treatment facilities is approximately 7 years.…”
mentioning
confidence: 98%
“…The most frequent complications were vertebral artery injury (65.1%) and intervertebral disc complications (22.5%) [13]. An extensive literature review by Ernst [4] focusing on chiropraxis complications revealed that the most frequent lesion reported was dissection of the vertebral arteries, and others included dural tear, edema, nerve injury, disc herniation, hematoma and bone fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The risk-benefit ratio with regard to manipulation of the cervical spine should be evaluated, as this procedure has been associated with mild to moderate adverse effects and serious adverse effects related to the vertebral artery 13) . To avoid such problems, mobilization and manipulation of another region of the spinal column, such as the thoracic spine, have been employed instead of cervical manipulation 7) .…”
Section: Introductionmentioning
confidence: 99%